PENGARUH EDUKASI GIZI BERBASIS BROSUR DAN POWER POINT TERHADAP TINGKAT PENGETAHUAN PEDOMAN GIZI SEIMBANG (PGS) SISWA KELAS VII MTs HAYATUL ILMI - Fitria Rahmawati (2020)
To have a health level with a good nutritional status, every country has guidelines that can be applied by its society as balanced nutrition guidelines. In this case, society has not been able to carry out a diet by focusing on balanced nutrition. Factors that affect the low nutritional knowledge due to the low socialization by providing knowledge of the Guidelines for Balanced Nutrition, known as Pedoman Gizi Seimbang (PGS) that have been applied by Indonesia Ministry of Health. Some ways can be used to improve an individual's knowledge, such as by providing nutrition education by using media as a supporting tool. This study aimed to determine the effect of nutrition education based on brochure and power point on the level of knowledge of the Balanced Nutrition Guidelines (BNG) in VII grade students of MTs Hayatul Ilmi. This study was a quasi experiment with a one group pretest-posttest design. The analysis used to process the data was a paired simple t-test statistical test. In the intervention group with brochure media education, the average pre-test score was 62.18, and after the intervention of knowledge on Balanced Nutrition Guidelines by using brochure media, the average post-test score was 71.03. While in the intervention group with power point media education, an average pre-test score of 59.03 was obtained, and after the intervention of knowledge on Balanced Nutrition Guidelines by using power point media, an average post-test score of 79.70 was obtained. This was supported by the results of the p-value of each educational media of 0.003 for the brochure media and 0.000 for the power point media.